2013
DOI: 10.1155/2013/894804
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Lower Cervical Bifurcation of the Common Carotid Artery

Abstract: Lower cervical bifurcation of cervical common carotid artery (CCA) is a very rarely encountered anatomic variation. Knowing the normal vascular anatomy and also its anomalies is important in preventing the vascular complications. Ill-defined vascular anomalies may lead to massive hemorrhage and eventually death during head and neck surgery. Imaging of the neck by magnetic resonance Imaging (MRI), CT, or angiography is helpful for diagnosis. We present a 62-year-old male patient diagnosed with laryngeal carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…during traction of the tissues to expose the disc spaces and insertion of the cages into the cervical interspaces) in a cervical dissection in a patient with low-lying CCA bifurcation. Uzun et al [7] reported a 62year-old male patient with bilateral lower cervical bifurcation of CCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…during traction of the tissues to expose the disc spaces and insertion of the cages into the cervical interspaces) in a cervical dissection in a patient with low-lying CCA bifurcation. Uzun et al [7] reported a 62year-old male patient with bilateral lower cervical bifurcation of CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons must be well-versed in anatomy of the great vessels of the neck and its anomalies before undertaking such an operation. Previously, in the literature, several carotid artery anomalies and anatomic variations which are agenesis, aplasia, hypoplasia, trifurcation, curved, kinked, anomalous origin, non-bifurcated cervical carotid artery, independent origins, aberrant artery, lower carotid bifurcation, and tortuosity were reported [1][2][3][4][5][6][7]. In some cases, bifurcation of common carotid artery (CCA) is seen lower than the usual localization, like lower cervical or thoracic bifurcation and tortuosity of carotid artery may be seen but in our knowledge, there has been no report in which tortuous internal carotid artery and lower cervical CCA bifurcation are co-existent.…”
Section: Introductionmentioning
confidence: 99%
“…The standard surgical carotid endarterectomy for atherosclerotic ICA disease is a complex procedure that requires a full understanding of all normal and potentially anomalous neck anatomy. 1 , 2 , 3 , 4 , 5 Variability of the right CCA bifurcation occurring below the cervical vertebra is an infrequent occurrence. Clinical reports suggest that the level at which the CCA bifurcates is most common at vertebral levels C3 to C5.…”
Section: Discussionmentioning
confidence: 99%
“…Variability of the CCA bifurcation can be found as high as C1 and as low as the thoracic inlet, with anatomic data demonstrating frequencies of high, normal, and low bifurcation locations as 31.2%, 57.5%, and 11.3%, respectively. 5 , 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation